Estudio de fallas y planteamiento de protecciones para sistemas de alta potencia basados en tecnología VSC-HVDC (2017)
"The scope of the project is the analysis of the strategies used for the substations control of A high power system based on VSC-HVDC technology, as well as presenting a methodology or device that protects the network and explains its operation." -- Tomado del Formato de Documento de Grado.